ASSOCIATION OF TRIGLYCERIDE / HIGH-DENSITY LIPOPROTEIN RATIO (TG/HDL RATIO) TO SPECIFIC RISK FACTORS OF DIABETES AND PREDIABETES - Nasution, Melati Silvanni; Pase, Muhammad Aron; Nasution, Ali Nafiah (TALENTA Publisher, Universitas Sumatera Utara, 2024)
Background: Diabetes is a group of metabolic diseases characterized by hyperglycemia due to defects in insulin secretion, insulin action, or both. Prediabetes is a precursor before the diagnosis of diabetes. Patients with prediabetes and diabetes have several risk factors, one of which is dyslipidemia. The TG/HDL ratio is found to be positively associated with insulin resistance and CVD. This study was conducted to determine whether there is a relationship between TG/HDL ratio and the incidence of prediabetes and diabetes. Method: This analytic cross-sectional study was conducted on July-December 2023. The study samples were prediabetic and diabetic patients who met the acceptance criteria of the study subjects. They were tested for BMI, BG, HbA1C and lipid profile. Data analysis used paired t test and Pearson correlation Result: In this study, BMI was greater in the prediabetes group than the diabetes group. There was a negative correlation between age, BG and HDL levels on TG/HDL ratio in prediabetic and diabetic patients. There was a significant relationship between fasting BG, 2 hours after meals BG, HbA1C and TG/HDL ratio when compared between the prediabetes and the diabetes group. Conclusion: In this study, there was no association between TG/HDL ratio in prediabetes and diabetes. Keywords: Prediabetes, diabetes, TG, HDL, HbA1c